The Degradation of Meritocratic Democracy: Political Determination of Gibran Rakabuming's Nomination Dynasty in the 2020 Solo Regional Head Elections - Hergianasari, Putri; Tabun, Diana S.A.N; Risal, Semuel (Kemudi, 2024)
This paper discusses the erosion of the meritocratic system in the victory of Gibran, Jokowi's son, who does not yet have sufficient political experience but advanced and won in the 2020 Solo regional head election by PDIP Party. The research aims to analyze the merit system in Gibran's candidacy and the embryonic political dynasty that Jokowi is trying to build. This study used descriptive qualitative method. data sources were obtained from literature and online data searches. This research uses the theory of Meritocracy Stephen J. McNamee and the concept of a political dynasty. This research results that the degradation of democracy comes from the inconsistency of Gibran's speech and behavior, this is a problem of political ethics. Gibran's advancement in the 2020 Solo contest shows the degradation of democracy in the institutional structure of the PDIP party because the phenomenon of Gibran's candidacy ignores meritocracy. The correlation between political parties, prospective candidates and constituents must be based on a merit system. In conclusion, Gibran's victory in the 2020 Solo Mayoral Election ignores meritocracy and is a degradation of democracy. The correlation between political parties, candidates and constituents is a mutually influential relationship to the practice of merit which is the basis for political contestation.